Positive pole piece, battery and electric equipment
By designing the first and second orthopedic activity layers of different carbon coverage in the orthopedic film, the problem of insufficient cycle performance and energy density of the secondary battery, and realized the positive pole film with high energy density and good cycle stability. Essence
Patent Information
- Application Number
- CN202310896329.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The circulation performance and energy density of existing commercial secondary batteries are difficult to meet the growth demand of the energy storage market, especially the performance of the positive electrode plate has a great impact.
A cathode plate is designed by arranging a first cathode active layer and a second cathode active layer with different carbon coating contents on the cathode current collector. Specifically, the mass proportion of the carbon coating material in the second cathode active material is Greater than the mass proportion of the carbon coating material in the first positive electrode active material, ranging from 1.5% to 6% and 0.5% to 3% respectively.
The positive electrode sheet has both high energy density and good cycle stability. It resists corrosion and reduces the dissolution of active ions by increasing the carbon coating content of the second positive electrode active layer, and at the same time by reducing the carbon coating content of the first positive electrode active layer. Cover content to increase gram capacity.
Smart Images

Figure CN119340393A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode sheet, a battery and an electrical device. Background Art
[0002] This section merely provides background information related to the present application and is not necessarily prior art.
[0003] Secondary batteries on the current market have attracted widespread attention for their advantages such as long life, safe use, and large capacity. With the rapid development of new energy vehicles and the gradual popularization of smart power stations, the current cycle performance and energy density of commercial secondary batteries are difficult to meet the growing demand of the energy storage market. Among them, the performance of the positive electrode has a crucial impact on the cycle performance and energy density of the battery. Therefore, the development of positive electrodes with good cycle performance and higher energy density has become a research focus. Summary of the invention
[0004] The main technical problem solved by this application is that the cycle performance and energy density of current commercial secondary batteries are difficult to meet the growing demand of the energy storage market.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode sheet, comprising:
[0006] Positive electrode current collector;
[0007] The first positive electrode active layer is at least located on one side of the positive electrode current collector; the first positive electrode active layer includes a first positive electrode active material, and the first positive electrode active material includes a first carbon coating material; based on the total mass of the first positive electrode active material, the mass percentage of the first carbon coating material is X 1 ;
[0008] The second positive electrode active layer is located on the side of the first positive electrode active layer away from the positive electrode current collector; the second positive electrode active layer includes a second positive electrode active material, and the second positive electrode active material includes a second carbon coating material; based on the total mass of the second positive electrode active material, the mass percentage of the second carbon coating material is X 2 ;
[0009] Among them, X 2 Greater than X 1 , X 2 The value range of X is 1.5%-6%. 1 The numerical range of meets 0.5%-3%.
[0010] In the embodiment of the present application, a first positive electrode active layer and a second positive electrode active layer with different carbon coating contents are arranged on the positive electrode current collector, so that the formed positive electrode plate has both high energy density and good cycle stability.
[0011] Specifically, by making the mass proportion of the carbon-coated material in the second positive electrode active material greater than the mass proportion of the carbon-coated material in the first positive electrode active material, on the one hand, the carbon-coated content of the active material in the second positive electrode active layer is relatively high, which is beneficial to resisting the corrosion of the second positive electrode active material by the electrolyte and the side reaction products, reducing the number of active ions dissolved from the second positive electrode active material, and reducing the situation where the dissolved active ions enter the negative electrode active material layer through the electrolyte to catalyze the growth of the negative electrode solid electrolyte membrane, thereby slowing down the decrease in the cycle capacity of the positive electrode plate and improving the cycle performance of the positive electrode plate; on the other hand, the carbon-coated content of the active material in the first positive electrode active layer is small, so that the gram capacity is higher, which is beneficial to the improvement of the energy density of the positive electrode plate.
[0012] In the embodiments of the present application, the percentage of the mass of the second carbon-coated material to the total mass of the second positive electrode active material is in the range of 1.5%-6%, so that the carbon coating content of the second positive electrode active material is relatively high, which is beneficial to resist the corrosion of the electrolyte and side reaction products to the second positive electrode active material, reduce the number of active ions dissolved from the second positive electrode active material, reduce the situation of the dissolved active ions entering the negative electrode active material layer through the electrolyte to catalyze the growth of the negative electrode solid electrolyte membrane, slow down the decline in the cycle capacity of the positive electrode plate, and the corresponding positive electrode plate has good cycle stability.
[0013] In an embodiment of the present application, the mass of the first carbon coating material accounts for a percentage of the total mass of the first positive electrode active material in the range of 0.5%-3%, so that the first positive electrode active material of the first positive electrode active layer has a higher gram capacity, and its corresponding positive electrode plate has a higher energy density.
[0014] In some embodiments, X 2 With X 1 The difference is less than or equal to 5%, which is beneficial to the improvement of the cycle performance and energy density of the positive electrode sheet.
[0015] In some embodiments, X 2 The numerical range meets 2%-3%.
[0016] In the embodiments of the present application, the mass of the second carbon-coated material accounts for 2%-3% of the total mass of the second positive electrode active material, and the corresponding positive electrode sheet has good cycle stability and good energy density.
[0017] In some embodiments, X 1 The numerical range of meets 0.8%-1.5%.
[0018] In the embodiment of the present application, the mass of the first carbon coating material accounts for a percentage of the total mass of the first positive electrode active material in the range of 0.8%-1.5%, and the corresponding positive electrode plate has a good energy density.
[0019] In some embodiments, the first carbon coating material has a greater degree of graphitization than the second carbon coating material.
[0020] In the embodiment of the present application, the degree of graphitization of the first carbon-coated material is greater than that of the second carbon-coated material. Compared with the second carbon-coated material, the first carbon-coated material has a higher degree of graphitization, fewer lattice defects, smaller resistance to electron migration, and better kinetic performance of the battery. Compared with the first carbon-coated material, the second carbon-coated material has a greater degree of disorder and more defects, which facilitates the embedding and extraction of active ions of the second positive electrode active material, helps reduce the occurrence of cyclic side reactions, and thus improves the cyclic performance of the corresponding positive electrode sheet.
[0021] In some embodiments, the Raman spectrum of the carbon coating material has a characteristic wavelength of 1350 cm -1 Peak and 1575cm -1 Peak, 1350cm -1 The peak height is ID, 1575cm -1 The peak height is IG; 1350cm -1 The peak height is 1575cm -1 The ratio of the peak heights of the peaks is ID / IG; (ID / IG) of the first carbon coating material 1 Smaller than (ID / IG) of the second carbon coating material 2 .
[0022] In the embodiments of the present application, the degree of graphitization of the second carbon-coated material is characterized by the characteristics of the Raman spectrum of the carbon-coated material to be less than the degree of graphitization of the first carbon-coated material. On the one hand, the characterization method can non-destructively characterize the degree of graphitization of the carbon-coated material. On the other hand, the characterization method can be carried out quickly and easily without the need for very harsh detection conditions. Furthermore, the spectral peaks of the carbon-coated material characterized by this method are clear and sharp, which is more suitable for quantitative research, database search, and qualitative research using differential analysis.
[0023] In some embodiments, the (ID / IG) of the second carbon coating material 2 (ID / IG) of the first carbon coating material 1 The ratio satisfies a value greater than 1 and less than or equal to 3; it can be selected as 1.2-2.5, which can achieve that the degree of graphitization of the first carbon-coated material is greater than the degree of graphitization of the second carbon-coated material.
[0024] In some embodiments, the (ID / IG) of the first carbon coating material1 The value range of meets 1.0-2.0.
[0025] In some embodiments, the (ID / IG) of the second carbon coating material 2 The value range of is 1.8-2.8.
[0026] In the embodiment of the present application, (ID / IG) of the first carbon coating material 1 The value range of is within the range of 1.0-2.0, so that the graphitization degree of the first carbon coating material is slightly higher, which is beneficial to improve the stability of the microstructure of the first positive electrode active material, reduce the shedding of the first positive electrode active material in the positive electrode sheet, and reduce the volume change of the first positive electrode active material caused by the embedding and extraction of active ions, which is beneficial to improve the energy density of the positive electrode sheet. In the embodiment of the present application, (ID / IG) of the second carbon coating material 2 The value range of is within the range of 1.8-2.8, so that the second carbon-coated material has a lower degree of graphitization, the second carbon-coated material has a larger degree of disorder, and the better the isotropy of the second carbon-coated material, the more conducive it is to the rapid embedding and extraction of active ions of the second positive electrode active material, thereby further improving the cycle performance of the corresponding positive electrode sheet.
[0027] In some embodiments, the first carbon encapsulating material includes amorphous carbon, and / or the second carbon encapsulating material includes amorphous carbon.
[0028] Among them, amorphous carbon refers to carbon materials with a low degree of graphitization and close to an amorphous state.
[0029] In the embodiments of the present application, the first carbon-coated material and / or the second carbon-coated material are formed by amorphous carbon, so that the first carbon-coated material and / or the second carbon-coated material have a lower degree of graphitization, the first carbon-coated material and / or the second carbon-coated material have a higher degree of disorder, and the first carbon-coated material and / or the second carbon-coated material have more defects, which facilitates the embedding and extraction of active ions of the first positive electrode active material and / or the second positive electrode active material, helps to reduce the occurrence of cyclic side reactions, thereby further improving the cycle performance of the corresponding positive electrode sheet.
[0030] In some embodiments, based on the same unit area, the mass ratio of the second positive electrode active layer to the first positive electrode active layer is m 2 / m 1 ;m 2 / m 1 The value range of m satisfies (2:8)-(7:3); Optionally, m 2 / m 1 The numerical range of satisfies (4:6)-(6:4).
[0031] In some embodiments, the mass ratio of the second positive electrode active layer to the first positive electrode active layer is in the range of (2:8)-(7:3), and the positive electrode plate has both good energy density and good cycle performance. It can be understood that if the mass ratio of the second positive electrode active layer to the first positive electrode active layer is too large, that is, the proportion of the second positive electrode active layer in the positive electrode plate is too large, and the proportion of the first positive electrode active layer in the positive electrode plate is too small, then the mass proportion of the carbon coating material of the positive electrode plate is too large, resulting in too small a proportion of the active material of the positive electrode plate, which in turn results in too low a gram capacity of the active material of the positive electrode plate, affecting the energy density of the positive electrode plate. If the mass ratio of the second positive electrode active layer to the first positive electrode active layer is too small, that is, the proportion of the second positive electrode active layer in the positive electrode plate is too small, the carbon coating material of the positive electrode plate has too little effect on improving the cycle performance. In the embodiments of the present application, the mass ratio of the second positive electrode active layer to the first positive electrode active layer is in the range of (4:6)-(6:4), and the positive electrode plate has both good energy density and good cycle performance.
[0032] In some embodiments, the mass per unit area of the first positive electrode active layer is 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 .
[0033] In some embodiments, the mass per unit area of the second positive electrode active layer is 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 .
[0034] In the embodiment of the present application, the mass per unit area of the first positive electrode active layer is 0.2g / 1540.25mm 2 -0.45g / 1540.25mm 2 In the embodiment of the present application, the mass per unit area of the second positive electrode active layer is 0.2g / 1540.25mm 2 -0.45g / 1540.25mm 2 Within the range of , the second positive electrode active layer 20 can maintain a certain energy density.
[0035] In some embodiments, the first positive electrode active material includes one or more of a layered structure material, a spinel structure material, and a polyanion material, which may be lithium iron phosphate; and / or the second positive electrode active material includes one or more of a layered structure material, a spinel structure material, and a polyanion material, which may be lithium iron phosphate.
[0036] In the embodiments of the present application, the first positive electrode active material and the second positive electrode active material may be one or a combination of the above-mentioned active materials, which have good cycle performance and safety performance.
[0037] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode sheet, comprising:
[0038] providing a positive electrode current collector;
[0039] A first positive electrode active layer is formed on one side of the positive electrode current collector; the first positive electrode active layer includes a first positive electrode active material, and the first positive electrode active material includes a first carbon coating material; based on the total mass of the first positive electrode active material, the mass percentage of the first carbon coating material is X 1 ;
[0040] A second positive electrode active layer is formed on a side of the first positive electrode active layer away from the positive electrode current collector; the second positive electrode active layer includes a second positive electrode active material, and the second positive electrode active material includes a second carbon coating material; based on the total mass of the second positive electrode active material, the mass percentage of the second carbon coating material is X 2 ; Among them, X 2 Greater than X 1 , X 2 The value range of X is 1.5%-6%. 1 The numerical range of meets 0.5%-3%.
[0041] In an embodiment of the present application, a layered positive electrode sheet is prepared, and a first positive electrode active layer and a second positive electrode active layer with different carbon coating contents are arranged on the positive electrode current collector, so that the formed positive electrode sheet has both high energy density and good cycle stability.
[0042] In some embodiments, a method for preparing the first positive electrode active material or the second positive electrode active material comprises:
[0043] mixing a precursor and a carbon source in a solvent, wherein the precursor includes a precursor material for forming a positive electrode active material;
[0044] Ball milling at a speed of 100r / min-1500r / min for 5h-20h;
[0045] After the mixture is dried, it is sintered at a temperature of 300° C. to 800° C. for 10 h to 24 h in an inert gas atmosphere.
[0046] The embodiments of the present application provide a method for preparing a positive electrode active material, and by regulating the mass content of the carbon source during the preparation process, a first positive electrode active material and a second positive electrode active material with different carbon coating contents are formed, so as to achieve a positive electrode sheet having both high energy density and good cycle stability.
[0047] In some embodiments, the carbon source includes one or more of an organic carbon source, carbon black, carbon nanotubes, and graphene; optionally, the organic carbon source includes one or more of sucrose, glucose, starch, citric acid, polyaniline, polyacrylic acid, and polyvinyl alcohol.
[0048] The carbon source can be one of the above materials or a combination of the above materials. The selection of the above materials can enable the carbon source to form a carbon-coated material with a low degree of graphitization, thereby increasing the disorder degree of the carbon-coated material and improving the isotropy of the carbon-coated material.
[0049] In a third aspect, an embodiment of the present application provides a battery, comprising any positive electrode sheet provided in the first aspect or a positive electrode sheet prepared by any preparation method provided in the second aspect.
[0050] In an embodiment of the present application, a battery includes a housing and a plurality of battery cells located in the housing. The housing is used to provide a storage space for the battery cells, and the housing may be in various shapes. In a battery, a plurality of battery cells may be connected in series, in parallel, or in a mixed connection. A plurality of battery cells may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the plurality of battery cells may be accommodated in the housing; of course, the battery may also be a battery module in which a plurality of battery cells are first connected in series, in parallel, or in a mixed connection, and a plurality of battery modules are then connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the housing. The battery may also include other structures. For example, the battery may also include a confluence component for realizing electrical connection between a plurality of battery cells. Each battery cell may be a secondary battery or a primary battery; it may also be a lithium-ion battery, a sodium-ion battery, or a magnesium-ion battery, but is not limited thereto.
[0051] In a fourth aspect, an embodiment of the present application provides an electrical device, comprising the battery provided in the third aspect.
[0052] An embodiment of the present application provides an electrical device, including the battery provided above. The electrical device may be a mobile phone, a computer, an electric motorcycle, an electric car, etc. This embodiment is illustrated by taking an electric car as an example. A battery is provided inside the electric car, and the battery may be provided at the bottom, head, or tail of the electric car. The battery may be used to power the electric car, for example, the battery may be used as an operating power source for the electric car. The electric car may also include a controller and a motor, and the controller is used to control the battery to power the motor, for example, for the starting, navigation, and working power requirements of the electric car during driving. In some embodiments of the present application, the battery can be used not only as an operating power source for the electric car, but also as a driving power source for the electric car, providing driving power for the electric car. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0054] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet provided in the embodiment of the present application;
[0055] Figure 2 is a schematic diagram of the structure of a battery provided in an embodiment of the present application;
[0056] Figure 3 is a schematic diagram of the specific structure of a battery cell provided in an embodiment of the present application;
[0057] Figure 4 It is a schematic diagram of the structure of the electrical equipment provided in the embodiment of the present application.
[0058] Figure 5 is a Raman spectrum of the first carbon coating material provided in an embodiment of the present application;
[0059] Figure 6 is a Raman spectrum of the second carbon coating material provided in the embodiments of the present application;
[0060] In the drawings, the drawings are not drawn to scale.
[0061] Marking Description:
[0062] 2000-electrical equipment, 1000-battery, 100-positive electrode plate, 200-negative electrode plate, 300-diaphragm, 400-battery cell, 500-case, 10-first positive electrode active layer, 20-second positive electrode active layer, 30-positive electrode current collector, 210-negative electrode current collector, 220-negative electrode active layer, 2001-controller, 2002-motor. DETAILED DESCRIPTION
[0063] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0064] During the long-term use of secondary batteries, the side reaction products of the electrolyte are easy to corrode the active materials of the positive electrode plates, causing the positive electrode active materials to dissolve active ions. The dissolved active ions enter the negative electrode active materials through the electrolyte and catalyze the growth of the negative electrode solid electrolyte membrane, accelerating the reduction of the cycle performance of the secondary battery. In addition, due to the dissolution of active ions in the positive electrode active materials, the gram capacity of the positive electrode plates decreases, further reducing the energy density of the secondary battery. Taking the secondary battery with lithium iron phosphate as the positive electrode active material as an example, the side reaction of the electrolyte and water produces hydrofluoric acid HF, which corrodes the lithium iron phosphate, causing iron ions to enter the electrolyte. The dissolution of iron ions catalyzes the growth of the negative electrode solid electrolyte membrane, resulting in the corresponding secondary battery The cycle capacity decays and the energy density is reduced.
[0065] In the embodiment of the present application, a first positive electrode active layer and a second positive electrode active layer are designed on the positive electrode plate, wherein the first positive electrode active layer comprises a first positive electrode active material, and the second positive electrode active layer comprises a second positive electrode active material. Different carbon coating designs are performed on the first positive electrode active material and the second positive electrode active material, so that the formed positive electrode plate has both high energy density and good cycle stability.
[0066] The technical solution described in the embodiments of this application is applicable to positive electrode sheets, batteries and electrical equipment. The technology disclosed in this application can be used for lithium-ion secondary batteries, sodium-ion secondary batteries or potassium-ion secondary batteries, and this application does not limit it.
[0067] The present application is described in detail below with reference to the accompanying drawings and embodiments.
[0068] See also Figure 1 , Figure 1 It is a schematic diagram of the structure of the positive electrode plate provided in an embodiment of the present application.
[0069] First, see Figure 1 The embodiment of the present application provides a positive electrode sheet 100, including a positive electrode current collector 30, a first positive electrode active layer 10 and a second positive electrode active layer 20. The first positive electrode active layer 10 is located at least on one side of the positive electrode current collector 30, and includes a first positive electrode active material. The first positive electrode active material includes a first carbon coating material. Based on the total mass of the first positive electrode active material, the mass percentage of the first carbon coating material is X 1 The second positive electrode active layer 20 is located on the side of the first positive electrode active layer 10 away from the positive electrode current collector 30, and includes a second positive electrode active material. The second positive electrode active material includes a second carbon coating material. Based on the total mass of the second positive electrode active material, the mass percentage of the second carbon coating material is X 2 Among them, X 2 Greater than X 1 , X 2 The value range of X is 1.5%-6%.1 The numerical range of meets 0.5%-3%.
[0070] In the embodiment of the present application, the positive electrode plate 100 is an important component of the secondary battery, which contains an active material that undergoes a reduction reaction during discharge. The positive electrode collector 30 represents a metal matrix for attaching active materials in the positive electrode plate 100. Taking a lithium-ion battery as an example, the positive electrode collector 30 can be made of aluminum metal. The first positive electrode active layer 10 represents a layered structure formed with the first positive electrode active material as the main material. In some embodiments, the first positive electrode active layer 10 is a layered film. In some embodiments, the positive electrode collector 30 has a first surface and a second surface that are arranged oppositely along its thickness direction. In some embodiments, the positive electrode plate 100 can be provided with a first positive electrode active layer 10 only on the first surface or the second surface of the positive electrode collector 30, or a first positive electrode active layer 10 can be provided on both the first surface and the second surface of the positive electrode collector 30. In some embodiments, the first positive electrode active layer 10 is directly arranged on the surface of the positive electrode collector 30, and in some other embodiments, other functional material layers are also arranged between the first positive electrode active layer 10 and the positive electrode collector 30. The first positive electrode active material refers to an active material that undergoes a reduction reaction during discharge. In an embodiment of the present application, the first positive electrode active material includes a first main material and a first carbon-coated material. The first main material may adopt any active material known in the art for secondary batteries. In some embodiments, the first main material may adopt one or more of a layered structure material, a spinel structure material, and a polyanionic material. For example, the layered structure material may be lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, a nickel-cobalt-manganese layered ternary material, or a lithium-rich manganese-based layered material. For example, the spinel structure material may be LiNi 0.5 Mn 1.5 O 4 For example, the polyanionic material may be LiFePO 4 , Li 3 V 2 (PO 4 ) 3 and / or LiFePO 4F. The first carbon coating material represents a carbon material formed on the surface of the first main material. In some embodiments, the first carbon coating material is coated on the surface of the first main material. In some embodiments, the first positive electrode active material is a particulate material, and in some embodiments, the average particle size of the particulate material is nanometer-scale or micrometer-scale. In some embodiments, the first positive electrode active layer 10 is formed by coating a slurry with the first positive electrode active material as the main material on the surface of the substrate. In some embodiments, in addition to the first positive electrode active material, the first positive electrode active layer 10 may also contain other additives, such as a binder, a conductive agent, and the like. Exemplarily, the binder of the first positive electrode active layer 10 may be materials such as polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC, polyacrylic acid PAA, carboxymethyl chitosan CMCs, polyacrylonitrile PAN, and polyvinyl alcohol PVA. Exemplarily, the conductive agent of the first positive electrode active layer 10 may be materials such as Ketjen black, carbon nanotubes, or graphene. The second positive electrode active layer 20 represents a layered structure formed with the second positive electrode active material as the main material. In some embodiments, the second positive electrode active layer 20 can be directly disposed on the surface of the first positive electrode active layer 10 away from the positive electrode current collector 30. In some embodiments, other functional material layers are also disposed between the second positive electrode active layer 20 and the first positive electrode active layer 10. In some embodiments, the second positive electrode active material includes a second main material and a second carbon coating material. In some embodiments, the second main material can be made of the same material as the first main material. In some embodiments, the second main material can be made of a material different from the first main material, and its material can also be made of one or more of a layered structure material, a spinel structure material, and a polyanionic material, which is different from the material of the first main material. The second carbon coating material represents a carbon material formed on the surface of the second main material. In some embodiments, in some embodiments, the second carbon coating material is coated on the surface of the second main material. The content of the first carbon coating material and the second carbon coating material is obtained according to the national standard DB35 / T 1558-2016 thermogravimetric analysis (TGA) test.
[0071] In the embodiment of the present application, a first positive electrode active layer 10 and a second positive electrode active layer 20 with different carbon coating contents are arranged on the positive electrode current collector 30 , so that the formed positive electrode sheet 100 has both high energy density and good cycle stability.
[0072] Specifically, by making the mass proportion of the second carbon-coated material in the second positive electrode active material greater than the mass proportion of the first carbon-coated material in the first positive electrode active material, on the one hand, the carbon-coated content of the active material in the second positive electrode active layer 20 is relatively high, which is beneficial to resisting the corrosion of the electrolyte and the side reaction products on the second positive electrode active material, reducing the number of active ions dissolved from the second positive electrode active material, and reducing the situation where the dissolved active ions enter the negative electrode active layer through the electrolyte to catalyze the growth of the negative electrode solid electrolyte membrane, thereby slowing down the decrease in the cycle capacity of the positive electrode plate 100 and improving the cycle performance of the positive electrode plate 100; on the other hand, the carbon-coated content of the active material in the first positive electrode active layer 10 is small, so that the gram capacity is higher, which is beneficial to the improvement of the energy density of the positive electrode plate 100.
[0073] For example, the percentage of the mass of the second carbon-coated material to the total mass of the second positive electrode active material can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, etc., or a range consisting of any two of the above values, such as 2%-2.5%, 2.5%-4%, 4.5%-6%, etc.
[0074] In the embodiments of the present application, the percentage of the mass of the second carbon-coated material to the total mass of the second positive electrode active material is in the range of 1.5%-6%, so that the carbon coating content of the second positive electrode active material is relatively high, which is beneficial to resist the corrosion of the electrolyte and side reaction products to the second positive electrode active material, reduce the number of active ions dissolved from the second positive electrode active material, reduce the situation of the dissolved active ions entering the negative electrode active material layer through the electrolyte to catalyze the growth of the negative electrode solid electrolyte membrane, slow down the decline in the cycle capacity of the positive electrode plate, and the corresponding positive electrode plate has good cycle stability.
[0075] For example, the percentage of the mass of the first carbon-coated material to the total mass of the first positive electrode active material can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc., or a range consisting of any two of the above values, such as 0.5%-1.5%, 1%-2.5%, 2%-3%, etc.
[0076] In an embodiment of the present application, the mass of the first carbon coating material accounts for a percentage of the total mass of the first positive electrode active material in the range of 0.5%-3%, so that the first positive electrode active material of the first positive electrode active layer has a higher gram capacity, and its corresponding positive electrode plate has a higher energy density.
[0077] In some embodiments, X 2 With X 1 The difference is less than or equal to 5%, which is beneficial to the improvement of the cycle performance and energy density of the positive electrode sheet 100.
[0078] For example, X2 With X 1 The difference can be 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., or a range consisting of any two of the above values, for example, 0-1.5%, 1.5%-3.5%, 3.5%-5%.
[0079] In some embodiments, X 2 With X 1 The ratio can be 1-7:3-9, which is beneficial to the improvement of the cycle performance and energy density of the positive electrode sheet 100.
[0080] For example, X 2 With X 1 The ratio can be 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, 4.5:5.5, 5:5, 5.5:4.5, 6:4, 6.5:3.5, 7:3, etc., or a range consisting of any two of the above values, for example, 4-6:6-4, 3-5:5-7, 5-7:3-5.
[0081] In some embodiments, X 2 The numerical range meets 2%-3%.
[0082] For example, the percentage of the mass of the second carbon-coated material to the total mass of the second positive electrode active material can be 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc., or a range consisting of any two of the above values, for example, 2%-2.4%, 2.4%-2.8%, 2.8%-3%, etc.
[0083] In the embodiment of the present application, the mass of the second carbon coating material accounts for a percentage of 2%-3% of the total mass of the second positive electrode active material, and the corresponding positive electrode plate 100 has good cycle stability and good energy density.
[0084] In some embodiments, X 1 The numerical range of meets 0.8%-1.5%.
[0085] For example, the percentage of the mass of the first carbon-coated material to the total mass of the first positive electrode active material can be 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc., or a range consisting of any two of the above values, such as 0.8%-1.2%, 1.2%-1.4%, 1.0%-1.5%, etc.
[0086] In the embodiment of the present application, the mass percentage of the first carbon coating material to the total mass of the first positive electrode active material is in the range of 0.8%-1.5%, and the corresponding positive electrode plate 100 has a good energy density.
[0087] In some embodiments, the first carbon coating material has a greater degree of graphitization than the second carbon coating material.
[0088] The degree of graphitization is an indicator that measures the degree to which carbon atoms form a close-packed hexagonal graphite crystal structure, reflecting the structural orderliness and electrical conductivity of carbon materials. The closer the lattice size of carbon atoms is to the lattice constant of ideal graphite, the higher the degree of graphitization and the fewer defects. The degree of graphitization is common knowledge in the art, has a definition known in the art, and can be measured by methods and instruments known in the art. In some embodiments, differences in the degree of graphitization can be achieved by selecting carbon coating materials with different degrees of graphitization. In other embodiments, differences in the degree of graphitization can also be achieved by adjusting the coating process.
[0089] In the embodiment of the present application, the degree of graphitization of the first carbon-coated material is greater than that of the second carbon-coated material. Compared with the second carbon-coated material, the first carbon-coated material has a higher degree of graphitization, fewer lattice defects, smaller resistance to electron migration, and better kinetic performance of the battery. Compared with the first carbon-coated material, the second carbon-coated material has a greater degree of disorder and more defects, which facilitates the embedding and extraction of active ions of the second positive electrode active material, helps reduce the occurrence of cyclic side reactions, and thus improves the cyclic performance of the corresponding positive electrode sheet.
[0090] In some embodiments, the Raman spectrum of the carbon coating material has a characteristic wavelength of 1350 cm -1 Peak and 1575cm -1 Peak, 1350cm -1 The peak height is ID, 1575cm -1 The peak height is IG, which refers to the distance from the maximum value of the characteristic peak to the bottom of the peak; 1350cm -1 The peak height is 1575cm -1 The ratio of the peak heights of the peaks is ID / IG; (ID / IG) of the first carbon coating material 1 Smaller than (ID / IG) of the second carbon coating material 2 .
[0091] The Raman spectrum of carbon-coated materials has a characteristic 1350cm -1 Peak and 1575cm -1 Peak, 1350cm -1 The peak height ID corresponds to the degree of defects in the carbon coating material, 1575 cm -1The peak height IG corresponds to the integrity of the carbon coating material. 1350cm -1 The peak height is 1575cm -1 The higher the peak height ratio ID / IG, the lower the graphitization degree of the carbon-coated material, the higher the disorder degree, the better the isotropy of the carbon-coated material, and the more conducive to the rapid deintercalation of active ions. -1 The peak height is 1575cm -1 The lower the ratio of the peak heights ID / IG, the higher the degree of graphitization and the lower the degree of disorder of the carbon coating material. 1 Smaller than (ID / IG) of the second carbon coating material 2 , indicating that the degree of graphitization of the first carbon-coated material is greater than that of the second carbon-coated material, and the degree of disorder is higher.
[0092] In the embodiments of the present application, the degree of graphitization of the second carbon-coated material is characterized by the characteristics of the Raman spectrum of the carbon-coated material to be less than the degree of graphitization of the first carbon-coated material. On the one hand, the characterization method can non-destructively characterize the degree of graphitization of the carbon-coated material. On the other hand, the characterization method can be carried out quickly and easily without the need for very harsh detection conditions. Furthermore, the spectral peaks of the carbon-coated material characterized by this method are clear and sharp, which is more suitable for quantitative research, database search, and qualitative research using differential analysis.
[0093] In some embodiments, the (ID / IG) of the second carbon coating material 2 (ID / IG) of the first carbon coating material 1 The ratio satisfies a value greater than 1 and less than or equal to 3; it can be selected as 1.2-2.5, which can achieve that the degree of graphitization of the first carbon-coated material is greater than the degree of graphitization of the second carbon-coated material.
[0094] For example, the (ID / IG) of the second carbon coating material 2 (ID / IG) of the first carbon coating material 1 The ratio can be 1.01, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, etc., or a range consisting of any two of the above values, for example, 1.2-1.8, 1.8-2.5, 2.5-3, etc.
[0095] In some embodiments, the (ID / IG) of the second carbon coating material 2 (ID / IG) of the first carbon coating material 1The difference satisfies that it is greater than 0 and less than or equal to 2; it can be selected as 0.3-1.5, which can achieve that the degree of graphitization of the first carbon-coated material is greater than the degree of graphitization of the second carbon-coated material.
[0096] For example, the (ID / IG) of the second carbon coating material 2 (ID / IG) of the first carbon coating material 1 The difference can be 0.01, 0.1, 0.3, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc., or a range consisting of any two of the above values, for example, 0.3-1.5, 1.5-2, 0.2-1.3, etc.
[0097] In some embodiments, the (ID / IG) of the first carbon coating material 1 The value range of meets 1.0-2.0.
[0098] In some embodiments, the (ID / IG) of the second carbon coating material 2 The value range of is 1.8-2.8.
[0099] In the embodiment of the present application, (ID / IG) of the first carbon coating material 1 The value range of is within the range of 1.0-2.0, so that the graphitization degree of the first carbon coating material is slightly higher, which is beneficial to improving the stability of the microstructure of the first positive electrode active material, reducing the shedding of the first positive electrode active material in the positive electrode plate 100, and reducing the volume change of the first positive electrode active material caused by the embedding and extraction of active ions, which is beneficial to improving the energy density of the positive electrode plate 100. For example, (ID / IG) of the first carbon coating material 1 The value of can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, etc., or a range consisting of any two of the above values, for example, 1.2%-1.4%, 1.5%-1.7%, 1.8%-1.9%, etc.
[0100] In the embodiment of the present application, (ID / IG) of the second carbon coating material 2 The value range of (ID / IG) is within the range of 1.8-2.8, so that the second carbon coating material has a lower degree of graphitization, the second carbon coating material has a larger degree of disorder, and the second carbon coating material has better isotropy, which is conducive to the rapid embedding and extraction of active ions of the second positive electrode active material, thereby further improving the cycle performance of the corresponding positive electrode sheet 100. For example, the (ID / IG) of the second carbon coating material is 2The value of can be 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, etc., or a range consisting of any two of the above values, for example, 2.0%-2.4%, 2.2%-2.6%, 2.4%-2.8%, etc.
[0101] It can be understood that in some embodiments, when the (ID / IG) of the first carbon coating material is 1 The value range of satisfies 1.0-2.0, and the (ID / IG) of the second carbon coating material 2 The value range of is greater than 2.0, which means that the graphitization degree of the first carbon-coated material is greater than the graphitization degree of the second carbon-coated material. In this case, the (ID / IG) of the second carbon-coated material 2 The value of can be greater than 2.0 and less than 2.8, or greater than 2.8. In some embodiments, when the (ID / IG) of the second carbon coating material is 2 The value range of the first carbon coating material is 1.8-2.8. 1 When the value of is less than 1.8, the graphitization degree of the first carbon-coated material can be greater than that of the second carbon-coated material. In this case, the (ID / IG) of the first carbon-coated material 1 The value of can be greater than 1.0 and less than 1.8, or less than 1.0. In some embodiments, the (ID / IG) of the first carbon coating material 1 The value range of satisfies 1.0-2.0, and the (ID / IG) of the second carbon coating material 2 The value range of satisfies 1.8-2.8, which is beneficial to improving the stability of the microstructure of the first positive electrode active material and the energy density of the positive electrode plate 100, and is also beneficial to making the isotropy of the second carbon-coated material as good as possible, which is beneficial to the rapid embedding and extraction of active ions of the second positive electrode active material, thereby further improving the cycle performance of the corresponding positive electrode plate 100.
[0102] In some embodiments, the first carbon encapsulating material includes amorphous carbon, and / or the second carbon encapsulating material includes amorphous carbon.
[0103] In the embodiments of the present application, the first carbon-coated material and / or the second carbon-coated material are formed by amorphous carbon, so that the first carbon-coated material and / or the second carbon-coated material have a lower degree of graphitization, the first carbon-coated material and / or the second carbon-coated material have a higher degree of disorder, and the first carbon-coated material and / or the second carbon-coated material have more defects, which facilitates the embedding and extraction of active ions of the first positive electrode active material and / or the second positive electrode active material, helps to reduce the occurrence of cyclic side reactions, thereby further improving the cycle performance of the corresponding positive electrode sheet.
[0104] In some embodiments, based on the same unit area, the mass ratio of the second positive electrode active layer 20 to the first positive electrode active layer 10 is m 2 / m 1 ;m 2 / m 1 The value range of m satisfies (2:8)-(7:3); Optionally, m 2 / m 1 The numerical range of satisfies (4:6)-(6:4).
[0105] In some embodiments, based on the same unit area, the mass ratio of the second positive electrode active layer 20 to the first positive electrode active layer 10 is in the range of (2:8)-(7:3), and the positive electrode plate 100 has both good energy density and good cycle performance. Within the above range, the mass ratio of the second positive electrode active layer 20 to the first positive electrode active layer 10 is relatively large, that is, the second positive electrode active layer 20 accounts for a large proportion of the positive electrode plate 100, which has a more obvious effect on improving the cycle performance of the battery cell. The mass ratio of the second positive electrode active layer 20 to the first positive electrode active layer 10 is relatively small, that is, the first positive electrode active layer 10 accounts for a large proportion of the positive electrode plate 100, which is conducive to the battery cell having a better energy density.
[0106] In the embodiment of the present application, based on the same unit area, the mass ratio of the second positive electrode active layer 20 to the first positive electrode active layer 10 is in the range of (4:6)-(6:4), and the positive electrode plate 100 has both good energy density and good cycle performance.
[0107] In some embodiments, the mass per unit area of the first positive electrode active layer 10 is 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 .
[0108] In some embodiments, the mass per unit area of the second positive electrode active layer 20 is 0.2 g / 1540.25 mm 2 -0.45 / 1540.25mm 2 .
[0109] In the embodiment of the present application, the mass per unit area of the first positive electrode active layer 10 represents the ratio of the total mass of the first positive electrode active material and other conductive materials in the first positive electrode active layer 10 to the extended area of the first positive electrode active layer 10. The mass per unit area of the first positive electrode active layer 10 is 0.2g / 1540.25mm 2 -0.45g / 1540.25mm 2In this way, the first positive electrode active layer 10 can maintain a certain energy density. For example, the mass per unit area of the first positive electrode active layer 10 can be 0.2 g / 1540.25 mm 2 , 0.25g / 1540.25mm 2 , 0.3g / 1540.25mm 2 , 0.35g / 1540.25mm 2 , 0.4g / 1540.25mm 2 , 0.45g / 1540.25mm 2 Or a range consisting of any two of the above values, such as 0.2%-0.3%, 0.3%-0.4%, 0.35%-0.45%, etc.
[0110] In the embodiment of the present application, the mass per unit area of the second positive electrode active layer 20 represents the ratio of the total mass of the second positive electrode active material and other conductive materials in the second positive electrode active layer 20 to the extended area of the second positive electrode active layer 20. The mass per unit area of the second positive electrode active layer 20 is 0.2g / 1540.25mm 2 -0.45g / 1540.25mm 2 In this way, the second positive electrode active layer 20 can maintain a certain energy density. For example, the mass per unit area of the second positive electrode active layer 20 can be 0.2 g / 1540.25 mm 2 , 0.25g / 1540.25mm 2 , 0.3g / 1540.25mm 2 , 0.35g / 1540.25mm 2 , 0.4g / 1540.25mm 2 , 0.45g / 1540.25mm 2 Or a range consisting of any two of the above values, such as 0.2%-0.3%, 0.3%-0.4%, 0.35%-0.45%, etc.
[0111] It can be understood that in some embodiments, when the value range of the unit area mass of the first positive electrode active layer 10 satisfies 0.2g / 1540.25mm 2 -0.45g / 1540.25mm 2 The mass per unit area of the second positive electrode active layer 20 may also satisfy 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 The numerical range may not meet 0.2g / 1540.25mm 2 -0.45g / 1540.25mm 2In some embodiments, when the value range of the mass per unit area of the first positive electrode active layer 10 satisfies 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 The mass per unit area of the second positive electrode active layer 20 also satisfies 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 In the case of a numerical range of, both the first positive electrode active layer 10 and the second positive electrode active layer 20 have good energy density, which is beneficial for the corresponding positive electrode sheet 100 to have good energy density.
[0112] In some embodiments, the first cathode active material includes one or more of a layered structure material, a spinel structure material, and a polyanion material, and may be lithium iron phosphate; and / or the second cathode active material includes one or more of a layered structure material, a spinel structure material, and a polyanion material, and may be lithium iron phosphate (Ferrous lithium phosphate, LiFePO 4 ).
[0113] The theoretical specific capacity of lithium iron phosphate is 170 mAh g -1 , the electrode potential relative to lithium is about 3.4V, and the theoretical energy density is 550Wh·kg -1 , the discharge capacity can reach 140mAh·g at a low current density -1 Lithium iron phosphate is stable during the charge and discharge process, and there is almost no need to consider the impact of temperature changes on the crystal structure, and it has good cycle performance. In addition, lithium iron phosphate also has advantages such as good safety and can be used in the field of new energy electric vehicles and energy storage.
[0114] In the embodiments of the present application, the first positive electrode active material and the second positive electrode active material may be one or a combination of the above-mentioned active materials, which have good cycle performance and safety performance.
[0115] It can be understood that in some embodiments, the first positive electrode active material and the second positive electrode active material use different active materials. In some embodiments, the first positive electrode active material and the second positive electrode active material both use the same active material, which, on the one hand, reduces the charge and discharge loss caused by the difference between the first positive electrode active material and the second positive electrode active material, and on the other hand, can only be achieved by adjusting the carbon coating content of the first positive electrode active material and the second positive electrode active material to distinguish the first positive electrode active layer 10 and the second positive electrode active layer 20. The first positive electrode active layer 10 and the second positive electrode active layer 20 can use the same batch of active materials, simplifying the process of the positive electrode sheet 100 and improving the stability of the product performance of the positive electrode sheet 100.
[0116] The embodiment of the present application provides a method for preparing a positive electrode sheet 100, comprising:
[0117] Providing a positive electrode current collector 30;
[0118] A first positive electrode active layer 10 is formed on one side of the positive electrode current collector 30; the first positive electrode active layer 10 includes a first positive electrode active material, and the first positive electrode active material includes a first carbon coating material; based on the total mass of the first positive electrode active material, the mass percentage of the first carbon coating material is X 1 ;
[0119] A second positive electrode active layer 20 is formed on a side of the first positive electrode active layer 10 away from the positive electrode current collector 30; the second positive electrode active layer 20 includes a second positive electrode active material, and the second positive electrode active material includes a second carbon coating material; based on the total mass of the second positive electrode active material, the mass percentage of the second carbon coating material is X 2 ; Among them, X 2 Greater than X 1 , X 2 The value range of X is 1.5%-6%. 1 The numerical range of meets 0.5%-3%.
[0120] In an embodiment of the present application, a layered positive electrode plate 100 is prepared, and a first positive electrode active layer 10 and a second positive electrode active layer 20 with different carbon coating contents are arranged on a positive electrode current collector 30, so that the formed positive electrode plate 100 has both high energy density and good cycle stability.
[0121] In some embodiments, a method for preparing the first positive electrode active material or the second positive electrode active material comprises:
[0122] Mixing a precursor and a carbon source in a solvent; the precursor includes a precursor material for forming a positive electrode active material;
[0123] Ball milling at a speed of 100r / min-1500r / min for 5h-20h;
[0124] After the mixture is dried, it is sintered at a temperature of 300° C. to 800° C. for 10 h to 24 h in an inert gas atmosphere.
[0125] The precursor includes a precursor material for forming a positive electrode active material. The carbon source is a raw material for forming a carbon coating material. The solvent refers to a liquid medium that contains the precursor and the carbon source. Ball milling is used to make the precursor and the carbon source fully contact. Sintering is used to make the carbon coating on the surface of the active material.
[0126] In any embodiment, the ball milling rate can be 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min, 1100r / min, 1200r / min, 1300r / min, 1400r / min, 1500r / min, or a range consisting of any two of the above values. For example, the ball milling rate can be 100r / min-500r / min, 500r / min-1000r / min or 1000r / min-1500r / min.
[0127] In any embodiment, the ball milling time can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, or a range consisting of any two of the above values. For example, the ball milling time can be 5h-10h, 10h-15h or 15h-20h.
[0128] In any embodiment, the sintering temperature can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, or a range consisting of any two of the above values. For example, the sintering temperature can be 300°C-500°C, 500°C-650°C or 600°C-800°C.
[0129] In any embodiment, the sintering time can be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, or a range consisting of any two of the above values. For example, the sintering time can be 10h-18h, 15h-20h or 18h-24h.
[0130] The embodiments of the present application provide a method for preparing a positive electrode active material, and by regulating the mass content of the carbon source during the preparation process, a first positive electrode active material and a second positive electrode active material with different carbon coating contents are formed, so as to achieve a positive electrode plate 100 having both high energy density and good cycle stability.
[0131] In some embodiments, the carbon source includes one or more of an organic carbon source, carbon black, carbon nanotubes, and graphene; optionally, the organic carbon source includes one or more of sucrose, glucose, starch, citric acid, polyaniline, polyacrylic acid, and polyvinyl alcohol.
[0132] The carbon source can be one of the above materials or a combination of the above materials. The selection of the above materials can enable the carbon source to form a carbon-coated material with a low degree of graphitization, thereby increasing the disorder degree of the carbon-coated material and improving the isotropy of the carbon-coated material.
[0133] See also Figure 2-Figure 3 , Figure 2 is a schematic diagram of the structure of a battery provided in an embodiment of the present application, Figure 3 It is a schematic diagram of the specific structure of a battery cell provided in an embodiment of the present application.
[0134] Second, see Figure 2-Figure 3 , an embodiment of the present application provides a battery 1000, comprising any positive electrode plate 100 provided in the first aspect.
[0135] In the examples of this application, see Figure 2 The battery 1000 includes a housing 500 and a plurality of battery cells 400 located in the housing. The housing 500 is used to provide a storage space for the battery cells 400, and the housing 500 can be in various shapes. In the battery 1000, the plurality of battery cells 400 can be connected in series, in parallel, or in mixed connection. Mixed connection means that the plurality of battery cells 400 are both connected in series and in parallel. The plurality of battery cells 400 can be directly connected in series, in parallel, or in mixed connection, and then the whole formed by the plurality of battery cells 400 is accommodated in the housing 500; of course, the battery 1000 can also be a battery module formed by first connecting a plurality of battery cells 400 in series, in parallel, or in mixed connection, and then the plurality of battery modules are connected in series, in parallel, or in mixed connection to form a whole, and then accommodated in the housing 500. The battery 1000 may also include other structures. For example, the battery 1000 may also include a converging component for realizing electrical connection between the plurality of battery cells 400. Each battery cell 400 may be a secondary battery or a primary battery; it may also be a lithium-ion battery, a sodium-ion battery or a magnesium-ion battery, but is not limited thereto.
[0136] In the embodiment of the present application, the battery cell 400 includes any positive electrode sheet 100 provided in the first aspect. Figure 3, the battery cell 400 includes a positive electrode sheet 100, a negative electrode sheet 200 and a separator 300. The positive electrode sheet 100 includes a positive current collector 30, a first positive active layer 10 and a second positive active layer 20. The first positive active layer 10 is located on the surface of the positive current collector 30 and includes a first positive active material. The first positive active material includes a first carbon coating material. The second positive active layer 20 is located on the surface of the first positive active layer 10 away from the positive current collector 30 and includes a second positive active material. The second positive active material includes a second carbon coating material. The negative electrode sheet 200 includes a negative current collector 210 and a negative active layer 220, and the negative active layer 220 is disposed on one surface of the negative current collector 210. The separator 300 is disposed between the positive electrode sheet 100 and the negative electrode sheet 200. In some embodiments, the material of the separator 300 may be PP (polypropylene) or PE (polyethylene), etc. In addition, the battery cell 400 may be a wound structure or a stacked structure.
[0137] See also Figure 4 , Figure 4 It is a schematic diagram of the structure of the electrical equipment provided in the embodiment of the present application.
[0138] Thirdly, see Figure 4 , an embodiment of the present application provides an electric device 2000, including the battery 1000 provided in the second aspect.
[0139] The embodiment of the present application provides an electric device 2000, including the battery 1000 provided above. The electric device 2000 can be a mobile phone, a computer, an electric motorcycle, an electric car, etc. This embodiment is described by taking an electric car as an example. A battery 1000 is arranged inside the electric car, and the battery 1000 can be arranged at the bottom, head or tail of the electric car. The battery 1000 can be used to power the electric car, for example, the battery 1000 can be used as an operating power supply for the electric car. The electric car may also include a controller 2001 and a motor 2002, and the controller 2001 is used to control the battery 1000 to power the motor 2002, for example, for the starting, navigation and working power requirements of the electric car during driving. In some embodiments of the present application, the battery 1000 can not only be used as the operating power supply of the electric car, but also as the driving power supply of the electric car, providing driving power for the electric car.
[0140] The beneficial effects of the present application are further illustrated below with reference to the embodiments.
[0141] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0142] A battery cell 400 is prepared, comprising the following steps:
[0143] Providing positive electrode sheet 100:
[0144] The positive electrode sheet 100 includes a positive electrode current collector 30, a first positive electrode active layer 10 and a second positive electrode active layer 20. The first positive electrode active layer 10 is located on the positive electrode current collector 30, and the unit area mass of the first positive electrode active layer 10 is 0.4 g / 1540.25 mm 2 , including a first positive electrode active material, the first positive electrode active material including a first main material and a first carbon coating material. The first main material is lithium iron phosphate. The first carbon coating material is amorphous carbon. Based on the total mass of the first positive electrode active material, the mass percentage of the first carbon coating material is 0.5%. (ID / IG) of the first carbon coating material 1 is 1.5, and its Raman spectrum is as follows Figure 5 As shown, it can be clearly seen that the first carbon coating material has a characteristic 1350cm -1 Peak and 1575cm -1 Peak, 1350cm -1 The peak height is about 2500, 1575cm -1 The peak height is about 1600, and the ratio of the two is about 1.5.
[0145] The second positive electrode active layer 20 is located on the side of the first positive electrode active layer 10 away from the positive electrode current collector 30, and its unit area mass is 0.4 g / 1540.25 mm 2 , including a second positive electrode active material, the second positive electrode active material including a second main material and a second carbon coating material. The second main material is lithium iron phosphate. The second carbon coating material is amorphous carbon. Based on the total mass of the second positive electrode active material, the mass percentage of the second carbon coating material is 1.5%. (ID / IG) of the second carbon coating material 2 is 2.5, and its Raman spectrum is as follows Figure 6 As shown, it can be clearly seen that the first carbon coating material has a characteristic 1350cm -1 Peak and 1575cm -1 Peak, 1350cm-1 The peak height is about 1300, 1575cm -1 The peak height is about 500, and the ratio of the two is about 2.5. The mass ratio of the second positive electrode active layer 20 to the first positive electrode active layer 10 is 3:7.
[0146] Providing negative electrode sheet 200:
[0147] The negative electrode sheet 200 includes a negative electrode current collector 210 and a negative electrode active layer 220. The negative electrode active layer 220 is located on the negative electrode current collector 210 and uses graphite as an active material. Its unit area mass is 0.350 g / 1540.25 mm 2 .
[0148] The positive electrode sheet 100, the separator 300, the negative electrode sheet 200, and the separator 300 are stacked and wound in sequence to form a battery cell, and then the battery cell 400 is obtained through processes such as tab welding, aluminum shell packaging, liquid injection, packaging formation, and vacuum molding. The battery cell 400 is left to stand at 45°C for 24 hours. The injected electrolyte is 1 mol / L LiPF 6 The solvent of the LiPF6 solution is ethylene carbonate EC and dimethyl carbonate DMC, and the volume ratio of the two is 1:2. The specific target components of each embodiment and comparative example are shown in Table 1.
[0149] The carbon coating materials of each layer of the positive electrode sheet 100 prepared in Examples 1-28 and Comparative Examples 1-2 were tested using an American Leica CS844 CS tester. After oxygen was purified, it was introduced into a combustion furnace. A certain mass of positive electrode active material samples were oxidized by oxygen at high temperature in the combustion furnace. The carbides in the samples were CO 2 , element analyzer by testing CO 2 The carbon coating amount is calculated based on the content.
[0150] The battery cells 400 prepared in Examples 1-28 and Comparative Examples 1-2 were subjected to a 2C cycle test at room temperature: the battery cells 400 in the Examples and Comparative Examples were taken to ensure that there were at least 2 parallel samples for each example. First, the battery cells 400 were placed in a constant temperature environment at 25°C for 1 hour. Then, the battery cells 400 were charged at a constant current at a charging rate of 2C, and switched to constant voltage charging after charging to 3.65V. Charging was stopped when the charging current was lower than 0.05C, and the battery was left for 5 minutes. Then, the battery was discharged at a constant current at a discharge rate of 1C to 2.5V, and left for 5 minutes. The above process was repeated for 1000 times, and the capacity retention rate was calculated as follows: the capacity retention rate of the 1000th cycle = the discharge capacity of the 1000th cycle / the discharge capacity of the second cycle * 100%. Energy density = battery capacity * voltage platform / battery weight (or battery volume). The test results are shown in Table 1.
[0151] Table 1 Performance test results of battery cells of the embodiment and comparative example
[0152]
[0153]
[0154] According to the results:
[0155] (1) According to the test data of Comparative Example 1 and Example 1, the cycle stability of the battery cell containing only one positive electrode active material is poor, and the cycle stability of the battery cell containing two layers of positive electrode active materials with different carbon coating contents and a lower degree of graphitization of the outer layer is greatly improved. According to the test data of Comparative Example 2 and Example 1, 2 Does not satisfy greater than X 1 Under these conditions, the cycle stability of the battery cell is poor.
[0156] (2) According to the test data of Examples 1-21, it can be seen that: 2 / m 1 , X 2 and X 1 When both are within the preferred range, the cycle stability of the battery monomer is better; 2 / m 1 , X 2 and X 1 When both are not within the preferred range, the cycle stability of the battery monomer is improved compared with the control ratio, but the improvement is limited; 2 / m 1 , X 2 and X 1 One of the two is in the preferred range and the other is not in the preferred range. The cycle stability of the battery cell is improved compared with the battery cell in which both are not in the preferred range, but the improvement is limited.
[0157] (3) According to the test data of Examples 22-26, it can be seen that: 2 / m 1 , X 2 and X 1 When both are within the preferred range, when the graphitization degree of the first carbon-coated material is constant, the lower the graphitization degree of the second carbon-coated material, the higher the cycle stability of the battery cell; when the graphitization degree of the second carbon-coated material is constant, the lower the graphitization degree of the first carbon-coated material, the higher the cycle stability of the battery cell.
[0158] (4) According to the test data of Examples 27-28, it can be seen that: 2 / m 1 , X 2 and X 1One of them is in the optional range, and the other is not in the optional range. The cycle stability of the battery cell is improved compared with the control ratio, but the improvement is limited.
[0159] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: include: Positive electrode current collector; a first positive electrode active layer, at least located on one side of the positive electrode current collector; the first positive electrode active layer comprises a first positive electrode active material, the first positive electrode active material comprises a first carbon coating material; based on the total mass of the first positive electrode active material, the mass percentage of the first carbon coating material is X1; A second positive electrode active layer is located on a side of the first positive electrode active layer away from the positive electrode current collector; the second positive electrode active layer comprises a second positive electrode active material, the second positive electrode active material comprises a second carbon coating material; based on the total mass of the second positive electrode active material, the mass percentage of the second carbon coating material is X2; Among them, X2 is greater than X1, the numerical range of X2 satisfies 1.5%-6%, and the numerical range of X1 satisfies 0.5%-3%.
2. The positive electrode sheet according to claim 1, characterized in that: The difference between X2 and X1 is less than or equal to 5%.
3. The positive electrode sheet according to claim 1, characterized in that: The numerical range of X2 satisfies 2%-3%, and / or the numerical range of X1 satisfies 0.8%-1.5%.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The graphitization degree of the first carbon coating material is greater than the graphitization degree of the second carbon coating material.
5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The Raman spectrum of carbon-coated materials has a characteristic 1350cm -1 Peak and 1575cm -1 Peak, 1350cm -1 The peak height is ID, and the 1575 cm -1 The peak height is IG; the 1350cm -1 The peak height is 1575cm -1 The ratio of the peak heights of the peaks is ID / IG; (ID / IG)1 of the first carbon coating material is smaller than (ID / IG)2 of the second carbon coating material.
6. The positive electrode sheet according to claim 5, characterized in that: The ratio of (ID / IG)2 of the second carbon coating material to (ID / IG)1 of the first carbon coating material satisfies greater than 1 and less than or equal to 3, and may be 1.2-2.
5.
7. The positive electrode sheet according to claim 6, characterized in that: The value range of (ID / IG)1 of the first carbon coating material satisfies 1.0-2.0; and / or The value range of (ID / IG)2 of the second carbon coating material satisfies 1.8-2.
8.
8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: The first carbon coating material includes amorphous carbon, and / or the second carbon coating material includes amorphous carbon.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: Based on the same unit area, the mass ratio of the second positive electrode active layer to the first positive electrode active layer is m2 / m1; the numerical range of m2 / m1 satisfies (2:8)-(7:3); optionally, the numerical range of m2 / m1 satisfies (4:6)-(6:4).
10. The positive electrode sheet according to claim 9, characterized in that: The mass per unit area of the first positive electrode active layer is 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 ; and / or The mass per unit area of the second positive electrode active layer is 0.2 g / 1540.25 mm 2 -0.45g / 1540.25mm 2 .
11. The positive electrode sheet according to claim 1, characterized in that: The first positive electrode active material includes one or more of a layered structure material, a spinel structure material, and a polyanion material, and may be lithium iron phosphate; and / or the second positive electrode active material includes one or more of a layered structure material, a spinel structure material, and a polyanion material, and may be lithium iron phosphate.
12. A method for preparing a positive electrode sheet, characterized in that: include: providing a positive electrode current collector; A first positive electrode active layer is formed on one side of the positive electrode current collector; the first positive electrode active layer includes a first positive electrode active material, and the first positive electrode active material includes a first carbon coating material; based on the total mass of the first positive electrode active material, the mass percentage of the first carbon coating material is X1; A second positive electrode active layer is formed on a side of the first positive electrode active layer away from the positive electrode current collector; the second positive electrode active layer includes a second positive electrode active material, and the second positive electrode active material includes a second carbon coating material; based on the total mass of the second positive electrode active material, the mass percentage of the second carbon coating material is X2; wherein X2 is greater than X1, the numerical range of X2 satisfies 1.5%-6%, and the numerical range of X1 satisfies 0.5%-3%.
13. The method for preparing a positive electrode sheet according to claim 12, characterized in that: The method for preparing the first positive electrode active material or the second positive electrode active material comprises: mixing a precursor and a carbon source in a solvent, the precursor comprising a precursor material for forming a positive electrode active material; Ball milling at a speed of 100r / min-1500r / min for 5h-20h; The obtained mixture is dried and then sintered at a temperature of 300° C. to 800° C. for 10 h to 24 h in an inert gas atmosphere.
14. The method for preparing a positive electrode sheet according to claim 13, characterized in that: The carbon source includes one or more of an organic carbon source, carbon black, carbon nanotubes, and graphene; optionally, the organic carbon source includes one or more of sucrose, glucose, starch, citric acid, polyaniline, polyacrylic acid, and polyvinyl alcohol.
15. A battery, characterized in that: It comprises the positive electrode sheet as described in any one of claims 1 to 11 or the positive electrode sheet prepared by the preparation method as described in any one of claims 12 to 14.
16. An electrical equipment, characterized in that: Comprising the battery of claim 15.
Citation Information
Patent Citations
Positive plate and preparation method thereof, electrode assembly, battery monomer, battery and electric equipment
CN115832182A
Lithium ion battery
CN116404253A
Positive electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery, battery module, and battery system using the same
JP7194299B1
Positive electrode active material and preparation method therefor, positive electrode plate, secondary battery, battery module, battery pack, and electrical device
WO2023115388A1
Cited By
Positive electrode material and battery
CN119905569A